Bare Life's Bare Essentials: When All You've Got is Hope – The State of Exception in The Road, District 9 and Blindness. (October 2014) - Bourke, Greg
This article operationalizes the work of Giorgio Agamben, through the prism of popular culture and filmic studies. Drawing extensively upon the cinematic experiences of The Road, District 9 and Blindness, a critique is formulated of this pre-eminent scholar's theory. Beginning with an analysis of the state of exception, Agamben's chilling assertions are examined. The remainder of the article then discusses the three films, as they provide the perfect vehicle for challenging Agamben's obsessions and contradictions. Although tied together by the common thread of the camp, the hidden matrix of modernity, each film occupies a distinct position along a spectrum of governmentality. Ultimately, what is exposed goes to the heart of the sensational, diabolical and disturbing world Agamben incarnates.